Sound Fragments: From Field Recording to African Electronic Stories - de Vries, Lee-Ann (International Library of African Music, 2023)
Review of: Sound Fragments: From Field Recording to African Electronic Stories. Noel Lobley, 2022. Middletown, Connecticut: Wesleyan University Press. 16 illustrations, bibliography, index. 348 pages. ISBN: 978-0-8195-8077-1
Keywords: Storytelling; Electronic music; Sound archives; Archives; Field Recording; African Music